2013
DOI: 10.1371/journal.pone.0059195
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Transformation of a Clinical (Genital Tract), Plasmid-Free Isolate of Chlamydia trachomatis: Engineering the Plasmid as a Cloning Vector

Abstract: Our study had three objectives: to extend the plasmid-based transformation protocol to a clinical isolate of C. trachomatis belonging to the trachoma biovar, to provide “proof of principle” that it is possible to “knock out” selected plasmid genes (retaining a replication competent plasmid) and to investigate the plasticity of the plasmid. A recently developed, plasmid-based transformation protocol for LGV isolates of C. trachomatis was modified and a plasmid-free, genital tract C. trachomatis isolate from Swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 35 publications
(25 reference statements)
1
50
0
Order By: Relevance
“…pORF deletion analysis revealed that Pgp1, -2, -6, and -8 are critical for plasmid maintenance and that Pgp4 is a transcriptional regulator of chlamydial gene expression and glycogen synthesis, while Pgp3, -5, and -7 are dispensable for chlamydial growth in vitro (16). Some of these observations were confirmed by Wang et al (17,18). This study was performed to further characterize chlamydial pORFs.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…pORF deletion analysis revealed that Pgp1, -2, -6, and -8 are critical for plasmid maintenance and that Pgp4 is a transcriptional regulator of chlamydial gene expression and glycogen synthesis, while Pgp3, -5, and -7 are dispensable for chlamydial growth in vitro (16). Some of these observations were confirmed by Wang et al (17,18). This study was performed to further characterize chlamydial pORFs.…”
supporting
confidence: 54%
“…As a proof of principle, we used the mCherry red fluorescent protein gene to replace pgp3, pgp4, and pgp5 and found that mCherry was successfully expressed regardless of the site of replacement. Similarly, Wang et al showed that ␤-galactosidase was expressed under the control of a chlamydial phage promoter when the ␤-galactosidase gene was used to replace pgp3 (18). Together, these observations have demonstrated the plasticity of the chlamydial plasmid as an expression vector.…”
Section: Figmentioning
confidence: 91%
“…Transformation of exogenous DNA into Chlamydia has been achieved via several methods, including electroporation, dendrimer-based delivery, and a calcium chloride-based treatment (14)(15)(16)(17)(18)(19). Successful and stable transformation of C. trachomatis LGV L2 with an Escherichia coli-C. trachomatis L2 shuttle plasmid conferring ␤-lactam resistance led to the development of expression vectors for expressing Chlamydia open reading frames (ORFs), fluorescent proteins (green fluorescent protein [GFP], cyan fluorescent protein [CFP], mCherry, and mKate2), and reporter proteins (␤-galactosidase, adenylate cyclase, and glycogen synthase kinase [GSK]-tagged proteins) (19)(20)(21)(22)(23)(24)(25)(26). A conditional expression vector was also developed using a tetracycline-inducible system as well as vectors conferring chloramphenicol and blasticidin resistance (21,(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Recently, we described the development of a transformation system for C. trachomatis that has been used by us, and subsequently by others, to modify the chlamydial plasmid and to begin to dissect the role of selected plasmid genes with regard to plasmid maintenance, host cell interactions, and in vitro phenotypic expression (e.g., inclusion morphology and glycogen accumulation) (14)(15)(16). In the present study, we further capitalize upon these findings and extend the transformation system to an analysis of in vivo plasmid-mediated pathobiology.…”
mentioning
confidence: 99%
“…Thus, we have hypothesized a role for plasmid CDS5 (pgp3) in directly affecting virulence, in vivo fitness, and induction of inflammatory responses. To test this hypothesis, we infected female mice in the urogenital tract or respiratory tract with either a naturally occurring plasmid(Ϫ) isolate; the same isolate transformed with a replication-competent vector containing plasmid CDSs (14), and the isolate transformed with the vector but with a knockout in CDS5 (pgp3) (15). Our results support the hypothesis that the product of the plasmid CDS5 (pgp3) gene plays a direct role in infectivity, in vivo fitness, and induction of host inflammatory responses.…”
mentioning
confidence: 99%